2022
DOI: 10.56286/ntujps.v1i2.175
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hashimoto's thyroiditis and its relationship to age, sex, smoking and blood groups.

Abstract: This study was aimed to demonstrate the incidence of  Hashimoto's disease in Iraqi patients and its correlation to some of the sociodemographic features. The research groups involved (50 patients with Hashimoto?s disease and 50 healthy subjects). All of them were subjected to the estimation of levels of free triiodothyronine (FT3), free thyroxine (FT4), TSH, anti-thyroid peroxidase (anti-TPO), and anti-thyroglobulin (anti-Tg). The results demonstrated that there is a dramatic increase in the occurrence of HT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…The thyroid hormones are responsible of the basal metabolic rate (BMR) in hypothyroid status the decrease in the T3 and T4 concentration lead to a lack in the rate of the metabolism and that's why hypothyroidisim causes obesity [27] Our Findings Showed a significant difference (decrease) in serum T3 levels (P≤ 0.011) and T4 levels (P≤0.001) and a significant increase in TSH levels (P<0.001) in hypothyroid patients compared to the control group as shown in These results agreed with other results [28] and [29] and also with [24], Chin and his assistants estimated that the raising of TSH levels in hypothyroid patients would be a compensative response to counteract the decrease levels of THs trying of hypothalamus to acquire into a homeostasis [30].…”
Section: Resultssupporting
confidence: 90%
“…The thyroid hormones are responsible of the basal metabolic rate (BMR) in hypothyroid status the decrease in the T3 and T4 concentration lead to a lack in the rate of the metabolism and that's why hypothyroidisim causes obesity [27] Our Findings Showed a significant difference (decrease) in serum T3 levels (P≤ 0.011) and T4 levels (P≤0.001) and a significant increase in TSH levels (P<0.001) in hypothyroid patients compared to the control group as shown in These results agreed with other results [28] and [29] and also with [24], Chin and his assistants estimated that the raising of TSH levels in hypothyroid patients would be a compensative response to counteract the decrease levels of THs trying of hypothalamus to acquire into a homeostasis [30].…”
Section: Resultssupporting
confidence: 90%
“…The results showed a significant increase in serum TSH levels (P<0.001) and a significant decrease in serum levels T4 (P ≤ 0.001) and T3 (P≤0.011) in hypothyroid patients compared to control group as shown in Table 1 These findings agreed with [25] and [26] and also with [27] Chin and his assistants estimated that the raising of TSH levels in hypothyroid patients would be a compensative response to counteract the decrease levels of THs trying of hypothalamus to acquire into a homeostasis [28].…”
Section: Resultssupporting
confidence: 87%
“…Tam Abass et al and Younus et al both reported a higher prevalence of thyroiditis among individuals with blood group O (57.3% and 52%, respectively) (21,32). A number of studies suggest that ABO blood type antigens may be associated with a general in ammatory response (33)(34)(35).…”
Section: Discussionmentioning
confidence: 97%